Mifepristone-Induced Hypothyroidism - Niketa Kalara MD; Alex Manzano MD (SAGE Publishing, 2023)
Medications are known to affect the thyroid physiology and are a known cause of hypothyroidism. There is an ever-growing list of medications that affect the thyroid by 1 or more mechanisms. Mifepristone is presently used for the treatment of mild autonomous cortisol secretion (MACS). Hypothyroidism is not a known side effect of this medication. We present a 71-year-old woman with newly diagnosed impaired fasting glucose, dyslipidemia, and osteopenia presenting with a 3-year history of unintentional 15-pound weight gain (despite exercise and a good diet) and increased anxiety. Her physical examination was pertinent for mild lower extremity edema, easy bruising, and skin thinning. Workup revealed adrenocorticotropic hormone (ACTH)-independent MACS from bilateral micronodular hyperplasia of the adrenals. Since she was not a surgical candidate, medical management with mifepristone was chosen. While on mifepristone, she complained of excessive fatigue, a workup done revealed new-onset hypothyroidism. Given her symptoms and bloodwork, she was started on levothyroxine. After stopping mifepristone, she was biochemically and clinically euthyroid and was eventually off levothyroxine. The mechanism by which mifepristone induces hypothyroidism is unknown. Except for a multicenter case series suggesting that mifepristone increases thyroid hormone requirements in patients with central hypothyroidism, to the best of our knowledge, the literature on euthyroid patients developing hypothyroidism secondary to mifepristone is scarce. In conclusion, while the hypothyroidism seems reversible our case highlights the importance of getting baseline thyroid function tests (TFTs) and repeating them while on the medication. Treatment of hypothyroidism is based on symptoms and bloodwork.